Mapping initial and general recombination in scanning proton pencil beams. (2nd June 2020) - Christensen, J B; Almhagen, E; Stolarczyk, L; Liszka, M; Hernandez, G G; Bassler, N; Nørrevang, O; Vestergaard, A
Abstract: The ion recombination is examined in parallel-plate ionization chambers in scanning proton beams at the Danish Centre for Particle Therapy and the Skandion Clinic. The recombination correction factor k s is investigated for clinically relevant energies between 70 MeV and 244 MeV for dose rates below 400 Gy min −1 in air. The Boutillon formalism is used to separate the initial and general recombination. The general recombination is compared to predictions from the numerical recombination code IonTracks and the initial recombination to the Jaffé theory. k s is furthermore calculated with the two-voltage method (TVM) and extrapolation approaches, in particular the recently proposed three-voltage (3VL) method. The TVM is in agreement with the Boutillon method and IonTracks for dose rates above 100 Gy min −1 . However, the TVM calculated k s is closer related to the Jaffé theory for initial recombination for lower dose rate, indicating a limited application in scanning light ion beams. The 3VL is in turn found to generally be in agreement with Boutillon's method. The recombination is mapped as a function of the dose rate and proton energy at the two centres using the Boutillon formalism: the initial recombination parameter was found to be A  = (0.10 ± 0.01) V at DCPT and A  = (0.22 ± 0.13) V at Skandion, which is in better agreement with the Jaffé theory for initial recombination than previously reported values. The general recombination parameter was estimated to m 2 = ( 4.7 ± 0.1 ) ⋅ 10 3 V 2 n A − 1 c m − 1 and m 2 = ( 7.2 ± 0.1 ) ⋅ 10 3 V 2 n A − 1 c m − 1 . Furthermore, the numerical algorithm IonTracks is demonstrated to correctly predict the initial recombination at low dose rates and the general recombination at high dose rates.